(untitled) (PANGRIPTA, 2024)
This research explores the role of local wisdom and the challenges posed by the COVID-19 pandemic in stunting prevention within the Arjowinangun community, Malang. Using a descriptive qualitative method, data were collected through interviews with parents of stunted children and healthcare workers, as well as through document analysis. The findings reveal that a lack of parental awareness and knowledge about stunting, compounded by the disruption of healthcare services during the pandemic, contributed to the persistent prevalence of stunting in the community. The pandemic further exacerbated the problem by causing interruptions in vital public health campaigns and community support systems. Misinformation surrounding COVID-19, fear of visiting healthcare facilities, and traditional practices not aligned with modern nutritional guidelines also hindered effective stunting prevention. This study underscores the need for enhanced education and culturally sensitive interventions that integrate local beliefs with evidence-based health strategies. By adopting a multifaceted approach that combines local knowledge, community engagement, and modern healthcare, efforts to combat stunting can be more effective, even in times of crisis.